2011
DOI: 10.1097/sap.0b013e3181f9b20c
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Advanced Age as a Risk Factor in Microvascular Breast Reconstruction

Abstract: Advanced age should not be considered a risk factor for microvascular breast reconstruction. Because ASA status did predict overall surgical complications, surgeons should consider the patients' overall health status in deciding whether to operate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 17 publications
6
54
1
Order By: Relevance
“…It is worth noting that in the present study, the rates of diabetes, smoking, and mean BMI are lower in our patients for both age groups than would be expected in the general population, and this is also true of other studies, 20,30 suggesting that there was a careful preoperative screening process that contributed to the overall success.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…It is worth noting that in the present study, the rates of diabetes, smoking, and mean BMI are lower in our patients for both age groups than would be expected in the general population, and this is also true of other studies, 20,30 suggesting that there was a careful preoperative screening process that contributed to the overall success.…”
Section: Discussionsupporting
confidence: 52%
“…35 Although there are many well-recognized physiological changes associated with advanced age, such as declines in cardiac, pulmonary, and renal function, recent studies have shown that age alone is not an independent predictor of poor postoperative outcome after major surgery, including head and neck, breast reconstruction, and microvascular flap reconstruction. 14,26,28,[30][31][32]38,39 Literature in this area is scarce; however, it does suggest that medical complications as opposed to surgical complications are often a cause of perioperative morbidity, and they are often a result of preexisting conditions as opposed to advanced age. 28,38 A more accurate predictor of morbidity and mortality is the American Society of Anesthesiologist physical status.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The ASA scoring system was the dominant system used in the literature (2)(3)(4)(5)(6)(8)(9)(10)(12)(13)(14)(17)(18)(19)(20). Three studies calculated CCI scores (3,21,22) and only one study used the KFI (11).…”
Section: Methodsmentioning
confidence: 99%